Saint Toribio de Mogrovejo, second archbishop ofLimaand patron saint oflatin american bishops - Alvarado Silva, Sergio (2009)
This distinguished pastor who sanctified himself in our country, not only did he prove to be a good minister, but be also tried to defend, value and respect the rights of natives within his diocese. Moreover, based on his civil law knowledge and applying what be had learned from the Council of Trent, and without forgetting his Deep spirituality, he knew how to live out a daily lije of faith in the fulfillment of God's will by helping the others according to the demands of his temporal context.That is why we begin with a briefbiography and then we will study his pastoral method, in other words his work plan which is based right on the Gospel, in its teaching, sanctifying and governing roles, as a good pastor, obedient and faithful to God's love and to that of others to whom he always showed humanly and honorable treatment in order to win their salvation.